Surgical correction of hallux valgus deformity in children with cerebral palsy - Ilker Abdullah Sarikaya; Ali Seker; Ozan Ali Erdal; Mehmet Ali Talmac; Muharrem Inan (Acta Orthopaedica et Traumatologica Turcica)
Objective: This study aimed to present a treatment algorithm for the correction of the hallux valgus deformity in Cerebral Palsy (CP) patients and to discuss the outcomes based on our clinical and radiological results. Methods: 29 patients (45 feet) were included in the study. The mean age of the patients at the time of the surgery was 14 (range 6–22) years. The mean follow-up was 33 (range 22–59) months. A reconstructive procedure was performed on 19 patients (27 feet); a soft tissue surgery and exostectomy of the bunion in six patients (11 feet); and MTP joint arthrodesis in four patients (7 feet). The hallux valgus angle (HVA) and the anteroposterior intermetatarsal angle (IMA) were used for radiologic evaluation and the DuPont Bunion Rating Score was used for clinical evaluation. Results: The follow-up period was 36 (range 22–59) months in reconstructive group, 27 (range 24–29) months in soft tissue group, and 29 (range 23–41) months in MTP arthrodesis group. Significant improvements were detected in hallux valgus angle in three groups postoperatively but in soft tissue group correction loss was observed during follow up. Best results were achieved in arthrodesis group and worse in soft tissue group in terms of clinical evaluation. Conclusion: According to our results isolated soft tissue procedures are ineffective in CP patients. Soft tissue procedure combined with metatarsal osteotomy has satisfactory results. Level of evidence: Level IV, therapeutic study. Keywords: Cerebral palsy, Hallux valgus, Surgical treatment, Toe deformity, Hallux valgus algorithm